2023
DOI: 10.3389/fneur.2022.1106358
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in acute ischemic stroke patients undergoing endovascular thrombectomy: Cervical internal carotid artery pseudo-occlusion vs. true occlusion

Abstract: Background and purposePseudo-occlusion of the cervical internal carotid artery (cICA) refers to an absence of intraluminal contrast on computed tomography angiography (CTA), while the artery is patent on digital subtraction angiography during endovascular thrombectomy. We aimed to compare the outcomes between the cICA pseudo-occlusion and true occlusion after thrombectomy.MethodsWe retrospectively analyzed patients with apparent cICA occlusion on CTA who underwent thrombectomy between January 2016 and August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…As suggested by multiple studies, pseudo-occlusion is a particularly unfavorable presentation of acute ischemic stroke in patients treated both with intravenous thrombolysis and mechanical thrombectomy [21][22][23][24]. These authors constantly reported lower revascularization rate in patients with pseudoocclusions after endovascular treatment, in contrast with our experience.…”
Section: Resultssupporting
confidence: 54%
“…As suggested by multiple studies, pseudo-occlusion is a particularly unfavorable presentation of acute ischemic stroke in patients treated both with intravenous thrombolysis and mechanical thrombectomy [21][22][23][24]. These authors constantly reported lower revascularization rate in patients with pseudoocclusions after endovascular treatment, in contrast with our experience.…”
Section: Resultssupporting
confidence: 54%
“…We set 5% as the value of type 1 error, 0.95 as the values of both sensitivity and specificity and 6% as the marginal error. Prevalence of 45% was determined from a recently published study by Ni et al 13 A sample size of 205 was acquired with 113 subjects for sensitivity and 92 for specificity.…”
Section: Methodsmentioning
confidence: 99%